2016
DOI: 10.1111/1556-4029.13110
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Forensic Utility of Scanning Electron Microscopy‐Energy Dispersive Spectroscopy and Laser Ablation‐Inductively Coupled Plasma‐Mass Spectrometry for Printing Ink Examinations

Abstract: Improvements in printing technology have exacerbated the problem of document counterfeiting, prompting the need for analytical techniques that better characterize inks for forensic analysis and comparisons. In this study, 319 printing inks (toner, inkjet, offset, and Intaglio) were analyzed directly on the paper substrate using scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) and Laser Ablation-Inductively Coupled Plasma-Mass Spectrometry (LA-ICP-MS). As anticipated, the high sensitivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…However, differentiation between manufacturers and/or identification of the printer associated with an inkjet or toner would enhance the probative value in determining the source of a questioned document. Williamson et al demonstrated the discrimination among the same set of printing inks using direct analysis real‐time mass spectrometry (DART‐MS) and attenuated total reflectance Fourier transform infrared spectroscopy (ATR‐FTIR), and Corzo et al also used the same set of ink samples to determine the discrimination power for scanning electron microscopy–energy‐dispersive spectrometry (SEM‐EDS) and laser ablation inductively coupled plasma mass spectrometry (LA‐ICP‐MS). Trejos et al also used the same set of ink samples to develop a searchable database incorporating data fusion of the above spectrochemical methods but excluding Raman microspectroscopy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, differentiation between manufacturers and/or identification of the printer associated with an inkjet or toner would enhance the probative value in determining the source of a questioned document. Williamson et al demonstrated the discrimination among the same set of printing inks using direct analysis real‐time mass spectrometry (DART‐MS) and attenuated total reflectance Fourier transform infrared spectroscopy (ATR‐FTIR), and Corzo et al also used the same set of ink samples to determine the discrimination power for scanning electron microscopy–energy‐dispersive spectrometry (SEM‐EDS) and laser ablation inductively coupled plasma mass spectrometry (LA‐ICP‐MS). Trejos et al also used the same set of ink samples to develop a searchable database incorporating data fusion of the above spectrochemical methods but excluding Raman microspectroscopy.…”
mentioning
confidence: 99%
“…The initial focus was to evaluate overall discrimination of the four selected printing inks. This approach also allowed for the direct comparison of the discrimination among the same set of printing inks in parallel studies using direct DART‐MS, ATR‐FTIR, SEM‐EDS, and LA‐ICP‐MS . Another focus was to determine the discrimination capability of Raman microspectroscopy to differentiate between inks of the same color within each of the four ink types, including the potential to discriminate ink brands of the same color.…”
mentioning
confidence: 99%
“…29 In the present study, the work was expanded to include colored toners and inkjets as well as two additional ink types: offset and intaglio. 16 The application of LA-ICP-MS to document examination has been fairly recent and is not currently widely adopted. 16,29,34…”
Section: Intaglio Printingmentioning
confidence: 99%
“…16 The application of LA-ICP-MS to document examination has been fairly recent and is not currently widely adopted. 16,29,34…”
Section: Intaglio Printingmentioning
confidence: 99%
“…For those toners, which did not have a known printer model, sample preparation was done by a deposition method to simulate the printout samples. The following steps were followed for the sample preparation 41,51 .…”
Section: Sample Preparation For Toner Printing Inksmentioning
confidence: 99%